2011
DOI: 10.1002/pssb.201046634
|View full text |Cite
|
Sign up to set email alerts
|

Nickel‐related defects in ZnO – A deep‐level transient spectroscopy and photo‐capacitance study

Abstract: Electronic defects in nickel-doped zinc oxide thin films have been investigated by means of capacitance spectroscopy. The samples were grown by pulsed laser deposition on a-plane sapphire substrates. Nickel was introduced into the films (a) during growth and (b) by implantation of Ni ions and subsequent thermal annealing. From deep-level transient spectroscopy it was concluded that a nickel-related trap, TNi2, with an energy level approximately 540 meV below the conduction band edge was formed. Photo-capacitan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
8
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 35 publications
1
8
0
Order By: Relevance
“…The implantation of zinc ions does not change the E3 concentration in HT bulk ZnO . The same result was reported for ZnO thin films: the implantation of zinc or nickel ions had no impact on the E3 defect density. Gu et al reported an increase of the E3 concentration in MG bulk ZnO samples after nitrogen ion implantation .…”
Section: Introductionsupporting
confidence: 79%
See 3 more Smart Citations
“…The implantation of zinc ions does not change the E3 concentration in HT bulk ZnO . The same result was reported for ZnO thin films: the implantation of zinc or nickel ions had no impact on the E3 defect density. Gu et al reported an increase of the E3 concentration in MG bulk ZnO samples after nitrogen ion implantation .…”
Section: Introductionsupporting
confidence: 79%
“…During warm‐up, the ions transfer back to the trivalent state X 3+ with thermal activation energies of 240 meV for Fe 2+ and 280 meV for Ni 2+ . Schmidt et al showed later that a nickel related state in ZnO had a higher thermal activation energy than E3. Vines and co‐workers studied the behavior of E3 in hydrothermal bulk material upon thermal annealing and compared it to the amount of impurities within the samples after each annealing step .…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…The knowledge on acceptor states in the vicinity of the valence band edge is scarce, see for example [13][14][15][16]. Junction capacitance techniques like deep-level transient spectroscopy (DLTS) [7,11,[15][16][17][18][19][20][21][22], deep-level optical spectroscopy (DLOS) [15], optical DLTS (ODLTS) [23] and photo-capacitance [16,22] have been used to study the properties of deep-levels in the zinc oxide band-gap. In doing so, knowledge on deep-levels was gained especially in the upper third of the zinc oxide band-gap.…”
mentioning
confidence: 99%